Polarization microvariability of BL Lacertae objects - Andruchow, Ileana (2005)
We present the results of a systematic observational campaign designed to search for microvariability in the optical polarization of BL Lac objects. We observed a sample formed by 8 X-ray-selected and 10 radio-selected sources, looking for rapid changes in both the degree of linear polarization and the corresponding polarization angle. The whole campaign was carried out during the last three years, and most of the objects were observed on at least two consecutive nights. The statistical properties of both classes of BL Lac objects are compared, and some general conclusions on the nature of the phenomenon are drawn. In general, radio selected sources seem to display higher duty cycles for polarimetric microvariability and, on average, they have a stronger polarization.